KOMPARASI HASIL BELAJAR EKONOMI ANTARA SISWA PENGURUS OSIS DENGAN NON PENGURUS OSIS MA AL-MUSTAQIM - Wulandari Wulandari; Nuraini Asriati; Bambang Genjik Sumartomo (Universitas Tanjungpura, 2020)
AbstractThe purpose of this study is to determine the differences of the learningoutcomes of economic subject between OSIS member students and nonOSIS member students of Madrasah Aliyah Al-Mustaqim KubuRaya. The population in this study was all students of class XI, which consist of 90 students. The sample in this study amounted to 30 students consisting of 15 OSIS member students and 15 non-OSIS member students, the sample was taken by using purposive sampling technique. This study used a quantitative approach to the type of comparison. The methods of data collection were done by observation, interview and documentation. The data analysis was using T-test analysis technique of SPSS for Windows Version 22.0 program. The results of the t-test showed tcount (3,415) > ttable (2,048) with a significance value of 0.05 and mean (61, 05 <71.21) which meant that there were differences of the learning outcomes of economic subject of the OSIS member students with non-OSIS member students, where the learning outcomes of OSIS member students are lower than non-OSIS member students however there are some students who the member of OSIS have high learning outcomes.Keywords: Learning Outcomes, Non-OSIS Members, OSIS Members